Amir evaluated 5x - (x + 3)2 for x = 2, as shown. Describe Amir's mistake and find the correct answer. 5(2) - (2 + 3)2 = 10 + (-5)2 = 10 + 25 = 35

Respuesta :


[tex]5 \times 2 - (2 + 3) \times 2 = 10 - 5 \times 2 = 10 - 10 = 0[/tex]

Answer with Step-by-step explanation:

We are given a expression:

[tex]5x - (x + 3)^2[/tex]

and we have to evaluate it at x=2

Putting x=2 in above expression, we get

[tex]5\times 2 - (2 + 3)^2\\\\=10-5^2\\\\=10-25\\\\=-15[/tex]

Amir's Calculation is as follows:

[tex]5(2) - (2 + 3)^2 = 10 + (-5)^2 = 10 + 25 = 35[/tex]

He took the minus sign before the bracket of (2+3)² inside the bracket

i.e. instead of writing -(2+3)²= -5²= -25

he wrote it as -(2+3)²= (-5)²

and the correct answer is:

-15

ACCESS MORE